2004
DOI: 10.1001/jama.292.18.2237
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Syndrome, Inflammation, and Risk of Cognitive Decline

Abstract: ARDIOVASCULAR AND METAbolic risk factors such as hypertension and diabetes have been hypothesized to play a role in the pathogenesis of Alzheimer disease (AD) as well as in development of vascular dementia. [1][2][3][4] The metabolic syndrome, 5 a clustering of several commonly occurring disorders that include (1) abdominal obesity, (2) hypertriglyceridemia, (3) low highdensity lipoprotein (HDL) level, (4) hypertension, and (5) hyperglycemia, has not been specifically investigated as a risk factor for cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
604
6
10

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 890 publications
(651 citation statements)
references
References 37 publications
31
604
6
10
Order By: Relevance
“…90 Diabetes could also impact cognition through its affects on blood glucose levels, insulin resistance, inflammation or alterations in beta-amyloid metabolism. [91][92][93] …”
Section: Discussionmentioning
confidence: 99%
“…90 Diabetes could also impact cognition through its affects on blood glucose levels, insulin resistance, inflammation or alterations in beta-amyloid metabolism. [91][92][93] …”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, a marker for insulin resistance and the main feature of MetS, may have direct negative effects on cognition, whereas such direct effects have not been discovered for the other components [23]. Another probable mechanism is the effect of the elevated inflammation often seen in patients with MetS [7,23] Markers of inflammation have been associated with an increased risk of cognitive decline and developing dementia [7]. Inflammation may also be viewed as part of MetS.…”
Section: Discussionmentioning
confidence: 99%
“…MetS is known to affect cognition, regardless of the mechanism, and evidence suggests that MetS, as a whole, is associated with declining cognitive function [4]. Although several studies have investigated the association between MetS and the risk of cognitive decline [5][6][7][8] in recent years, the effect of MetS on the rate of cognitive decline remains controversial [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, we observed an association between cognitive impairment and IR even though children with OSA symptoms were excluded from the study. Previous reports have revealed that IR-related disorders, such as the metabolic syndrome and type-2 diabetes, are also associated with neurocognitive dysfunction [30,31] and it has been suggested that the effects of IR on CNS function are probably due to the abnormalities in vascular reactivity to insulin [32]. Specifically, if a defined region of the brain is activated during cognitive functioning, this activation causes local vasodilatation to clear metabolic products [33]; however, an endothelial damage due to IR can impair such regional vasodilatation [34].…”
Section: Discussionmentioning
confidence: 99%